From Isolation to Interaction: Group Counseling as a Pathway to Better Social Skills in Young Learners - Rihana, Nisa; Wita, Arsyizahma; Gonzales, Amantha (Journal of Early Childhood Education and Teaching (JECET), 2025)
Purpose – This study aims to evaluate the effectiveness of group counseling programs in improving social relationships among early childhood learners. Social interaction is a critical developmental domain in early childhood, contributing to emotional regulation, collaboration, and empathy.Design/methods/approach – The study employed a quantitative approach using a pretest-posttest design. The intervention was conducted through structured group counseling sessions tailored to the developmental stage of early childhood learners. Data collection involved observation sheets and social interaction rating scales administered before and after the program. The effectiveness of the intervention was measured using statistical analysis of the changes in children's social behavior indicators.Findings – The findings revealed a significant improvement in the social relationships of early childhood learners following their participation in the group counseling sessions. Indicators such as cooperation, communication, and empathy showed marked increases. The structured group setting facilitated peer bonding, emotional expression, and problem-solving skills among the children.Research implications/limitations – The study is limited by its sample size and duration of implementation. It focused on a specific age group in a controlled educational setting. Future research should explore diverse educational contexts, include broader participant demographics, and consider longitudinal analysis to examine the sustained impact of group counseling.Originality/value – This research emphasizes the importance of group counseling as a viable method for enhancing the social development of young children. It offers practical insights for early childhood educators and counselors seeking developmentally sensitive strategies to promote positive peer relationships and socio-emotional growth.